Statistical yearbook for Asia and the Pacific 2008. (United Nations Publication, 2008)
This is the second issue of the new Statistical Yearbook for Asia and the Pacific. The format was revised in 2007 and attracted encouraging feedback from readers. It is aimed at a non-specialized audience that is interested in this dynamic and diverse region and wishes to see how the economies, societies and environment of Asia and the Pacific are developing in comparison with other world regions. Rich in information content, the Yearbook includes data, charts and a textual overview of well over 200 indicators, covering all spheres of the work of the Economic and Social Commission for Asia and the Pacific, as well as such cross-cutting issues as poverty and gender. The baseline year for the data is 1990 intentionally the same as that for the Millennium Development Goals, so the Yearbook can also be used for tracking progress towards the Goals. The Yearbook uses the internationally comparable data available at the time of publication. For more recent estimates and forecasts, readers can also consult another ESCAP publication, the Economic and Social Survey of Asia and the Pacific. (Source: www.unescap.org)